Human forces and their impact on the formation of Islamic political thought. (Journal of Misan Researches, 2024)
In this study , we seek to show the extent of the contribution of human forces and their impact on the formation of Islamic political thought, as the source of ruling power in the development of some Islamic political theories, as well as determining the course of governance and setting certain mechanisms for it, which contributed effectively to defining the Islamic political system ruling long historical periods that extended in some aspects to the present time, from this point of view, the researcher followed the historical approach descriptive and analytical and accordingly divided into three sections preceded by an introduction where the first section of which is related to the concept of human forces and development , and the second section was entitled the impact of human forces in the establishment of Islamic political theories and finally came the third section on the impact of human forces in the mechanisms of choosing the ruler and then followed by the conclusion and the list of sources and references.